Relations among sorghum ergot strains from the United States, Mexico, Puerto Rico, Bolivia, India and Australia - Pazoutova, S.; Bandyopadhyay, Ranajit; Frederickson, D.E.; Mantle, P.G.; Frederiksen, R.A. (2000)
Sorghum ergot, initially restricted to Asia and Africa, was recently found in the Americas and Australia. Three species causing the disease have been reported: Claviceps sorghi in India, C. sorghicola in Japan, and C. africana in all ergot-positive countries. The objective of our study was to study the intraspecific variation in C. africana isolates in the Americas, Africa, India, and Australia. We confirmed C. africana, C. sorghi, and C. sorghicola as different species using differences in nucleotide sequences of internal transcribed spacer 1 and 5.8S rDNA regions. Sequences of this region obtained from the representative American, Indian, and Australian isolates of C. africana were identical. In addition, random amplified polymorphic DNA (RAPD) banding patterns of sorghum ergot pathogen isolates from the United States, Mexico, Puerto Rico, Bolivia, Australia, and India were evaluated with nearly 100 primers. A total of 65 primers gave identical patterns for all isolates, which confirmed that all were C. africana. The identity of RAPD pattern and rDNA sequence of Indian isolates with those of C. africana confirmed that the species is now present in India. Only 20 primers gave small pattern differences and 7 of them were used for routine testing. All of the American isolates were identical and three isolates of the same type were also found in South Africa, suggesting Africa as the origin of the invasion clone in the Americas. Australian and Indian isolates were distinguishable by a single band difference; therefore, migration from the Asian region to Australia is suspected. Another distinct group was found in Africa. Cluster analysis of the informative bands revealed that the American and African group are on the same moderately (69%) supported clade. Isolates from Australia and India belonged to another clade.